A New Era of Nuclear Criticality Experiments: The First 10 Years of Comet Operations at NCERC. (5th November 2021) - Thompson, Nicholas; Sanchez, Rene; Goda, Joetta; Amundson, Kelsey; Cutler, Theresa; Grove, Travis; Hayes, David; Hutchinson, Jesson; Kostelac, Cole; McKenzie, George; McSpaden, Alexander; Myers, William; et al.
Abstract: Comet is a general-purpose, heavy-duty, vertical-lift assembly designed for flexibility in conducting a variety of critical experiments. It is currently located at the National Criticality Experiments Research Center (NCERC) in Nevada. In the past, Comet resided at Technical Area-18 in Los Alamos, New Mexico, as part of the Los Alamos Critical Experiments Facility (LACEF). The Comet assembly was relocated to NCERC in 2008 and became fully operational in June of 2011. The first critical experiment performed on Comet at NCERC was a verification of one of the previous configurations of the Zeus experiment series. Over the next 10 years, many additional experiments followed including other Zeus configurations as well as completely new designs. This paper discusses the Comet vertical-lift assembly, the transition from LACEF to NCERC, and a selection of experiments that have been performed on Comet during its first 10 years of operation at NCERC.